Food systems transformation in Zimbabwe: Effectiveness of participatory monitoring and evaluation - Tinarwo, Joseph; Jarbandhan, Vain D.B; Gwiza, Aaram (New Agenda: SA Journal of Social and Economic Policy, 2024)
The usefulness of participatory monitoring and evaluation (PM&E) in food systems transformation in Africa remains poorly explored. JOSEPH TINARWO, VAIN JARBANDHAN and AARAM GWIZA explain how PM&E is designed to measure programme effectiveness and is geared towards promoting programme ownership, empowering beneficiaries, enhancing transparency and accountability, and improving the projects and programmes. However, they caution that the effectiveness of PM&E in food system transformation requires adequate budgetary support, rolling capacity-building initiatives, multistakeholder partnerships, policy integration, and indigenous knowledge-sharing and learning practices.